Phytochemical characterization and antioxidant potential of Allium ursinum L. cultivated on different soil types- a preliminary study - Stefan, Gordanić; Dragoja, Radanović; Sandra, Vuković (Emirates Journal of Food and Agriculture, 2023)
Wild garlic (Allium ursinum L.) has been used as nutrition and medicine for centuries. Although this plant species is a typical spring geophyte that grows spontaneously in moist, steep, shady beech forests, but information on phytochemical and antioxidant properties under various soil types are scarce. This study aimed to assess the phytochemical composition and antioxidant potential of the leaves of A. ursinum grown on different soil types, but under identical climatic conditions of South Banat, Serbia. For the purpose of reproduction, A. ursinum bulbs were collected from two different locations in Serbia and then planted on different types of soil, namely: Arenosol, Fluvisol, Cambisol and Chernozem. Fresh leaves of sprouted plants were sampled at the beginning of spring, morphologically analysed and stoma was counted. The leaf extract was prepared and its phytochemical composition and antioxidant potential were assessed. Regardless of the origin of the reproductive material (bulbs), the leaves of A. ursinum plants cultivated in Chernozem soil had the best morphological characteristics and the largest number of stomata. Phytochemical analyses revealed the following ranges for selected bioactive compounds (expressed on fresh weight, FW): chlorophyll content (289.9-642.4 μg/g for chlorophyll a i.e. 358.2-458.6 μg/g for chlorophyll b), total carotenoid content (TCC, 91.2-263.2 μg/g), total phenolic content (TPC, 1.43-1.98 mg/g GAE), total flavonoid content (TFC, 0.36-1.28 mg/g QE), and total dihydroxycinnamic acid derivative content (HCA, 0.53-0.59 mg/g CGAE). The highest values were obtained on Chernozem (chlorophyll a, chlorophyll b and TPC and HCA) and Cambisol (TCC and TFC). Chernozem appeared to be the best soil type during three applied standard antioxidant assays (CUPRAC, TAC and FRP) while DPPH radical quenching assay revealed no significant differences among all examined soil types. Based on the obtained results it could be assumed that Chernozem exhibited the most desirable physico-chemical properties for optimal development of A. ursinum (in particular its green parts) as a source of different antioxidants. Correlation analysis of phytochemical parameters has proved significant influence of total chlorophylls, phenolics, flavonoids and duhydroxycinnamic acid derivatives on antioxidant activity of A. ursinum leaves (unlike total carotenoid content) with the highest correlation between HCA and FRP assay (r2= 1.00). In addition, PCA analysis clearly determined Chernozem type of soil as the best choice for optimal leaf growth and development.